2008
DOI: 10.1002/iroh.200711054
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Controls the Phosphorus Release from Lake Sediments – a Long‐Lasting Paradigm in Limnology

Abstract: The pioneer works of EINSELE, MORTIMER, and OHLE on the linking between phosphorus (P) and iron (Fe) cycles seven decades ago created the theoretical basis for a long-standing paradigm among limnologists i.e., 'oxygen controls the P release from sediments'. While many empirical studies as well as strong correlations between oxygen depletion and P release seem to support this paradigm, various field observations, laboratory experiments, and repeated failures of hypolimnetic oxygenation measures cast doubt on it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
321
2
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 476 publications
(338 citation statements)
references
References 77 publications
11
321
2
4
Order By: Relevance
“…On the one hand, this may relate to changes in the inputs by the different sources relative to each other (e.g., different ratios between P loads of individual rivers compared to N loads). On the other hand, selected processes (e.g., nitrification) cannot be considered in case of P labeling, while other processes such as P release from the sediment under anoxic conditions would play an additional role when considering P (e.g., Hupfer and Lewandowski, 2008). However, this process is not included in ECOHAM as it is designed primarily to represent the O 2 cycle in relation to N and C. As N constitutes the limiting nutrient among these two with respect to organic matter production, we focused our analysis on N. In order to assess the overall impact of nutrients (i.e., N and P) from individual sources on the North Sea O 2 dynamics, an analogous analysis for P would be required.…”
Section: Limitations Of the Model Intrinsics And The Tbnt Methodsmentioning
confidence: 99%
“…On the one hand, this may relate to changes in the inputs by the different sources relative to each other (e.g., different ratios between P loads of individual rivers compared to N loads). On the other hand, selected processes (e.g., nitrification) cannot be considered in case of P labeling, while other processes such as P release from the sediment under anoxic conditions would play an additional role when considering P (e.g., Hupfer and Lewandowski, 2008). However, this process is not included in ECOHAM as it is designed primarily to represent the O 2 cycle in relation to N and C. As N constitutes the limiting nutrient among these two with respect to organic matter production, we focused our analysis on N. In order to assess the overall impact of nutrients (i.e., N and P) from individual sources on the North Sea O 2 dynamics, an analogous analysis for P would be required.…”
Section: Limitations Of the Model Intrinsics And The Tbnt Methodsmentioning
confidence: 99%
“…In shallow lakes, internal P loading was widely regarded as a great source of nutrient (Welch and Cooke 1995;Nürnberg and LaZerte 2004;Steinman et al 2009). However, internal nutrient released from sediment is often related to anoxia (Hupfer and Lewandowski 2008). There has been a number of reports confirmed that phosphorus release from bottom sediments was dominant by anoxic conditions (Andersen and Ring 1999, James and Barko 1991, Steinman et al 2009, Welch and Cooke 1995.…”
Section: Comparison With Other Regionsmentioning
confidence: 99%
“…The most likely interpretation is that PC-3 represents the redox conditions in the bottom waters, where less oxygen in the bottom waters would favor the incorporation of S as sulfides in the sediment (Holmer and Storkholm, 2001;Leng et al, 2012). For P, the opposite behavior would be expected, with oxic conditions favoring incorporation of P bound to iron hydroxides and oxyhydroxides, and anoxic or hypoxic conditions resulting in dissolution of iron hydroxides and a release of P to the water column (Davison, 1993;Hupfer and Lewandowski, 2008). This interpretation would also fit with the down-core variation in PC-3 scores where positive scores are mainly associated with unit Ia, but also to some extent with unit IIIb (Fig.…”
Section: Discussionmentioning
confidence: 99%